Uniting communities: harnessing social capital for community resilience during coronavirus disease 2019 - Alfitri, Alfitri; Taqwa, Ridhah; Budiyanto, Mumahammad Nur; Nadjib, Abdul; Santoso, Anang Dwi (Intelektual Pustaka Media Utama, 2024)
This research investigates the impact of both traditional and virtual social capital on community resilience, with engagement on social media as a mediating variable. The study surveyed 397 inhabitants of an urban sub-district in Palembang, Indonesia, and analyzed the data using the structural equation model partial least square (SEM-PLS) technique. The results indicate that it is critical to prioritize and activate various forms of social capital to enhance community resilience during the coronavirus disease 2019 (COVID-19) pandemic. The analysis showed that social media engagement had a significant positive impact on community resilience (p<0.05), however the influence of virtual bonding social capital was negligible and negatively skewed (p=0.084). It is significant to note that community resilience was significantly positively impacted by both traditional bonding and bridging social capital (both p<0.05). Social media involvement was also markedly positively impacted by virtual bonding and bridging social capital (both p<0.05). The link between virtual bonding, bridging social capital, and community resilience was strongly influenced by social media use in terms of mediation (both p<0.05). This emphasizes how important social capital, both physical and digital, and particularly social media participation, are to building community resilience during pandemics.